Denervation of pulmonary artery during mitral valve surgery in patients with high pulmonary hypertension - А. В. Богачев-Прокофьев; С. И. Железнев; А. В. Афанасьев; М. С. Фоменко; Д. П. Демидов; Р. М. Шарифулин; А. Н. Пивкин; Д. А. Астапов; Е. И. Семенова; С. Н. Иванов; А. М. Караськов (Патология кровообращения и кардиохирургия, 2016)
Objective. Pulmonary hypertension impairs the mitral valve and often leads to more severe symptoms of heart failure, low exercise tolerance and thus higher rates of morbidity and mortality. The purpose of this study is to evaluate the safety and efficacy of simultaneous radiofrequency ablation of ganglionated plexi of the pulmonary artery in patients with high pulmonary hypertension during mitral valve surgery. Methods. The inclusion criteria were based on patients’ echocardiography/right heart catheterization data. The main criteria were mean pulmonary artery pressure ≥40 mm Hg at rest and a positive reactive test with nitric oxide inhalation. From January 2014 to May 2015, 14 patients underwent radiofrequency denervation of the pulmonary artery in addition to planned mitral valve surgery. Mean patient age was 53.4±7.8 years, with 57.1% of patients being females. Results. Mean cardiopulmonary bypass time was 116±12 minutes, mean cross-clamp time was 95±13 minutes, and mean ablation time amounted to 9.5±3.1 minutes. Pulmonary artery pressure decreased significantly from a mean of 56.5±9.8 mmHg to 32.0±7.3 mmHg immediately after the operation (p<0.001), and to 28.4±5.2 mmHg and 29.7±4.4 mmHg on the first and third days at ICU respectively. Mean ICU stay was 3.1±1.2 days. There were neither early deaths nor specific complications. Conclusions. Simultaneous radiofrequency ablation of pulmonary artery ganglionated plexi when performing mitral valve surgery in patients with pulmonary hypertension is a safe and effective procedure. Further research and long-term follow-up would help to determine whether a decrease in the mean pressure of the pulmonary artery can be interpreted as a clinical advantage.